Utilization of Duck Feet Gelatin with the Additional Glycerol as A Plasticizer on the Physical Properties of Edible Film - Hana Aulia Andiati; Jajang Gumilar; Eka Wulandari (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
The packaging that is widely used is plastic packaging, but this material has a weakness that is difficult to decompose and isn’t biodegradable, therefore edible film can be an alternative primary packaging for food products. The material used consists of gelatine made from duck feet with the addition of various concentrations of glycerol. Duck feet is an underutilized portion of the animal's anatomy, yet they contain collagen, which has the potential to be the raw material for gelatine and edible films. The study was undertaken utilizing duck feet as a source of raw material, which was subsequently processed into gelatine for use in the production of edible films using different glycerol treatments. The treatments comprised of glycerol concentrations of P1 = 10%, P2 = 20%, P3 = 30%, P4 = 40%, P5 = 50%, and P6 = 60%. The findings indicated that the application of glycerol significantly affected the films' solubility, water absorption, and tensile strength (P<0.05), but didn’t significantly affect the elongation of edible films. (P>0.05). The optimal concentration of glycerol for edible film in this study was obtained by using 20% glycerol, with a physical characteristic value of 40.25% solubility, 24.23% water absorption, tensile strength is 0.57 MPa, and elongation is 90%.